(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
The Barongan traditional dance is not merely a folkloric entertainment spectacle, but rather an educational medium rich in philosophical, aesthetic, and psychomotor values. This study aims to analyze the process of internalizing Barongan artistic values and its impact in stimulating children’s emotional expression and creativity. Using a qualitative approach with a case study method, data were collected through participatory observation of children’s activities in dance studios, in-depth interviews with art educators, and documentation of children’s expressive behavior. The results show that internalization of Barongan artistic values occurs through three main stages: value transformation (recognition of characters and movement patterns), value transactions (interactive practice processes), and transinternalization (characterization). The dynamic, spontaneous, and expressive character of Barongan provides a safe space for children to channel emotions, reduce anxiety, and explore body movements freely. This research makes a significant contribution to the field of early childhood education and arts pedagogy by demonstrating that traditional dance can serve as an integral instrument for psychological stimulation. These findings highlight the practical application of Barongan art in fostering emotional regulation, kinesthetic intelligence, and original and independent thinking in children. Furthermore, this research provides a model for cultural preservation that goes beyond passive conservation, positioning traditional art as a dynamic and relevant tool for holistic child development in the modern era.